2018
DOI: 10.1021/acs.orglett.8b02301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2-Oxazinanes via Hydrogen Bond Mediated [3 + 3] Cycloaddition Reactions of Oxyallyl Cations with Nitrones

Abstract: Reported herein is the development of [3 + 3] cycloaddition reactions between oxyallyl cations and nitrones to yield 1,2-oxazinane heterocycles. Oxyallyl cation intermediates, generated in situ from α-tosyloxy ketones in the presence of hexafluoro-2-propanol (HFIP), a cosolvent, and a base, are found to react with a range of nitrones to afford 1,2-oxazinanes in good to high yields. The reactions are catalyzed by hydrogen-bond donors such as phenols and squaramides, and dramatically higher diastereoselectivitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Our previouss tudies showed that thiourea L1 [10] and squaramide L2 [11] (Scheme 1) are suitable additives for the bulk electrolysis of [Cp 2 Ti(IV)Cl 2 ]i nT HF and the use of the resulting solutions for radical arylation.T he CVs (L1:F igure 1; L2:F igure 2) highlight the reasons for this assessment. Compared to the CV of [Cp 2 Ti(IV)Cl 2 ]w ithout additives (black traces), the oxidation waves pertaining to [Cp 2 Ti(III)Cl 2 ] À have ar educed intensity and that of [Cp 2 Ti(III)Cl] an increased intensity.T his effect is significantly more pronouncedf or L2 than for L1.W ea ssumed that these effects predict as uccessful bulk electrolysis and catalytic radicalarylation.…”
Section: Cyclic Voltammetry and Radical Arylationmentioning
confidence: 99%
“…Our previouss tudies showed that thiourea L1 [10] and squaramide L2 [11] (Scheme 1) are suitable additives for the bulk electrolysis of [Cp 2 Ti(IV)Cl 2 ]i nT HF and the use of the resulting solutions for radical arylation.T he CVs (L1:F igure 1; L2:F igure 2) highlight the reasons for this assessment. Compared to the CV of [Cp 2 Ti(IV)Cl 2 ]w ithout additives (black traces), the oxidation waves pertaining to [Cp 2 Ti(III)Cl 2 ] À have ar educed intensity and that of [Cp 2 Ti(III)Cl] an increased intensity.T his effect is significantly more pronouncedf or L2 than for L1.W ea ssumed that these effects predict as uccessful bulk electrolysis and catalytic radicalarylation.…”
Section: Cyclic Voltammetry and Radical Arylationmentioning
confidence: 99%
“…Gratefully, this protocol using 10 mol% of 1d and 2 equivalents of DMAP delivered 3a in same yield (entry 15). None or only trace of nitrone was observed in the absence of photosensitizer 1, DMAP, or oxygen (entries [16][17][18]. However, when the reaction was carried out in the dark, the desired product was isolated in 52% yield (entry 19).…”
Section: Letter Synlettmentioning
confidence: 99%
“…In parallel, Rawal et al reported a similar oxyallyl cation based strategy towards 1,2-oxazinanes (Scheme 16b). 35 However, it requires over stoichiometric amount of base, higher temperature and longer reaction time. Through further investigation, Rawal et al also showed that inexpensive pnitrophenol can be used as a hydrogen bond donor catalyst in DCE solvent to promote the [3+3] cycloaddition reactions with improved diastereoselectivity (Scheme 16c).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%